Similar Healthcare Utilization and 1-Year Patient-Reported Outcomes between Cemented and Cementless Primary Total Knee Arthroplasty: A Propensity Score-Matched Analysis - Erossy, Michael P.; Emara, Ahmed K.; Rothfusz, Christopher A.; Klika, Alison K.; Bloomfield, Michael R.; Higuera, Carlos A.; Jin, Yuxuan; Krebs, Viktor E.; Mesko, Nathan W.; Molloy, Robert M.; Murray, Trevor G.; Patel, Preetesh D.; Stearns, Kim L.; Schaffer, Jonathan L.; Strnad, Gregory J.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2021)
Cementless fixation for total knee arthroplasty (TKA) has gained traction with the advent of newer fixation technologies. This study assessed (1) healthcare utilization (length of stay (LOS), nonhome discharge, 90-day readmission, and 1-year reoperation); (2) 1-year mortality; and (3) 1-year joint-specific and global health-related patient-reported outcome measures (PROMs) among patients who received cementless versus cemented TKA. Patients who underwent cementless and cemented TKA at a single institution (July 2015–August 2018) were prospectively enrolled. A total of 424 cementless and 5,274 cemented TKAs were included. The cementless cohort was propensity score-matched to a group cemented TKAs (1:3-cementless: n = 424; cemented: n = 1,272). Within the matched cohorts, 76.9% (n = 326) cementless and 75.9% (n = 966) cementless TKAs completed 1-year PROMs. Healthcare utilization measures, mortality and the median 1-year change in knee injury and osteoarthritis outcome score (KOOS)-pain, KOOS-physical function short form (PS), KOOS-knee related quality of life (KRQOL), Veteran Rand (VR)-12 mental composite (MCS), and physical composite (PCS) scores were compared. The minimal clinically important difference (MCID) for PROMs was calculated. Cementless TKA exhibited similar rates of median LOS (p = 0.109), nonhome discharge disposition (p = 0.056), all-cause 90-day readmission (p = 0.226), 1-year reoperation (p = 0.597), and 1-year mortality (p = 0.861) when compared with cemented TKA. There was no significant difference in the median 1-year improvement in KOOS-pain (p = 0.370), KOOS-PS (p = 0.417), KOOS-KRQOL (p = 0.101), VR-12-PCS (p = 0.269), and VR-12-MCS (p = 0.191) between the cementless and cemented TKA cohorts. Rates of attaining MCID were similar in both cohorts for assessed PROMs (p > 0.05, each) except KOOS-KRQOL (cementless: n = 313 (96.0%) vs. cemented: n = 895 [92.7%]; p = 0.036). Cementless TKA provides similar healthcare-utilization, mortality, and 1-year PROM improvement versus cemented TKA. Cementless fixation in TKA may provide value through higher MCID improvement in quality of life. Future episode-of-care cost-analyses and longer-term survivorship investigations are warranted.
Keywords: cemented; cementless; fixation; total knee arthroplasty (TKA); healthcare utilization; patient-reported outcomes